2016
DOI: 10.1177/1533034616685025
|View full text |Cite
|
Sign up to set email alerts
|

A Dose–Volume Response Model for Brain Metastases Treated With Frameless Single-Fraction Robotic Radiosurgery: Seeking to Better Predict Response to Treatment

Abstract: Purpose/Objective(s):To establish a dose–volume response relationship for brain metastases treated with single-fraction robotic stereotactic radiosurgery and identify predictors of local control.Materials/Methods:We reviewed a prospective institutional database of all patients treated for intact brain metastases with stereotactic radiosurgery alone using the CyberKnife robotic radiosurgery system from 2012 to 2015. Tumor response was determined based on Response Evaluation Criteria In Solid Tumors version 1.1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Finally, they observed that patients with fewer number of metastases had worse local control (OR: 0.815, 95% CI: 0.72-0.93). 8 Similar observation was made by Yamamoto et al in their study on stereotactic radiosurgery for multiple brain metastases. 9 They observed significant difference in local recurrence ratio and need for repeat treatment between group with 2-9 metastases (more recurrences) and group with 10 and more lesions.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Finally, they observed that patients with fewer number of metastases had worse local control (OR: 0.815, 95% CI: 0.72-0.93). 8 Similar observation was made by Yamamoto et al in their study on stereotactic radiosurgery for multiple brain metastases. 9 They observed significant difference in local recurrence ratio and need for repeat treatment between group with 2-9 metastases (more recurrences) and group with 10 and more lesions.…”
Section: Discussionsupporting
confidence: 73%
“…Amsbaugh et al used the dose per lesion diameter and dose per volume parameters to construct dose-volume response relationships. 7,8 They found strong correlation between doses and volumes of the tumor which was quite obvious because all patients in their series were treated with single fraction, so the larger the volume, the smaller total dose was used. This resulted with worse results in patients with larger metastases who were treated with lower doses.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This creates a dose profile inside the target that is relatively inhomogeneous, which has been shown to improve local control. 4 Recent work has verified that significant improvements in gradient can be achieved by increasing dose inhomogeneity inside the target for various platforms. 21,22,24,29,34 As a result, the majority of radiosurgery practitioners are aligned with this treatment philosophy, and the indices proposed in this study encourage the use of this philosophy.…”
Section: Discussionmentioning
confidence: 99%
“…. [4] It is possible to calculate OARh 50% for any delineated structure. When multiple surrounding structures are delineated, the calculated OARh 50% values can be used as a guide for preferentially sparing radiosensitive surround-…”
Section: Efficiency Index For Oarsmentioning
confidence: 99%